Towards valuation of the mangrove reserve and wildlife sanctuary of Barotac Nuevo, Iloilo rationale, techniques, and considerations - Bagsit, Farisal U. (Iloilo City UP Visayas, 2010)
"Resource degradation has serious implications on our country's coastal and marine resources, e.g. mangroves. Like many environmental resources, the goods and services derived from a mangrove ecosystem are not traded in the market; thus, benefits derived from these resources are often not recognized (Spaninks & van Beukering, 1997) and are unaccounted for. Consequently, policy makers and resource managers often encounter difficulty in imposing a more realistic fine for violations or making a rational decision for developmental projects that would impact the environment. It is essential to understand and recognize the full value of mangrove resources not only to ensure their proper management but also to provide a sound basis for development planning in the different areas of the country. This paper aims to discuss the rationale and considerations in valuing the different aspects of economic and environmental benefits generated by the mangrove resources in the Mangrove Reserve and Wildlife Sanctuary (MRWS) of Barotac Nuevo, Iloilo. It further explores the valuation techniques deemed most appropriate in valuing the uses and benefits that are provided by these mangrove resources."
Keywords: Coastal zone management -- Iloilo City; Mangrove Reserve and Wildlife Sanctuary (MRWS).